Characterization of Fuel Produced from Nylon (Polyamide) and Polyethylene Terephthalate (PET) Wastes with Pyrolysis - Oyeyemi T. AFOROLAGBA-BALOGUN; Olumide A. TOWOJU (FUDMA Journal of Engineering and Technology, 2025)
The escalating accumulation of plastic waste, particularly polyethylene terephthalate (PET) and Polyamide (PA), poses significant environmental challenges due to their non-biodegradable nature and the limitations of conventional disposal methods. Pyrolysis, a thermochemical decomposition process conducted in the absence of oxygen, offers a promising alternative by converting plastic waste into valuable liquid fuels, gases, and char. This technique not only helps to mitigate the environmental burden of plastic pollution but also contributes to the circular economy by recovering energy-rich products from post-consumer polymers. This study explores the potential of pyrolysis as a sustainable thermochemical process to convert PET and PA waste into valuable liquid fuels. The resulting fuels were subjected to comprehensive characterization to assess their physicochemical properties. Comparative analyses between PET and PA-derived fuels were performed to evaluate their respective properties and potential applications. The findings revealed that the PET-PA blended oil yielded slightly higher calorific value (47.55 MJ/kg) compared to pure PA oil (46.75 MJ/kg), indicating a richer energy profile. However, the PA oil showed superior fuel behaviour in terms of volatility and ignition with a lower flash point and higher fire point PET/PA[13.74ºC and 263ºC] as compared to the PA(15.82 °C and 294 °C). The volatile content of both oils was comparably high (85.5%), but the fixed carbon and ash contents were lower in the PET-PA blend, suggesting cleaner combustion. Additionally, both fuels showed density values (1.12 g/cm³ for PA and 1.10 g/cm³ for PET/PA) above conventional gasoline which is (0.71-0.77g/cm3), indicating higher molecular weight fractions. The sulphur content remained under 1% in both cases. These results demonstrate the feasibility of transforming plastic waste into usable liquid fuel, contributing to both sustainable waste management and alternative energy generation. The findings indicate that pyrolysis offers a viable pathway for mitigating plastic pollution while contributing to sustainable energy production, aligning with global sustainability goals.
Keywords: Nylon-derived liquid fuel, plastic waste management, polyethylene terephthalate, pyrolysis.